2022
DOI: 10.3390/brainsci12020181
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an IL-4-Related Gene Risk Signature for Malignancy, Prognosis and Immune Phenotype Prediction in Glioma

Abstract: Background: Emerging molecular and genetic biomarkers have been introduced to classify gliomas in the past decades. Here, we introduced a risk signature based on the cellular response to the IL-4 gene set through Least Absolute Shrinkage and Selection Operator (LASSO) regression analysis. Methods: In this study, we provide a bioinformatic profiling of our risk signature for the malignancy, prognosis and immune phenotype of glioma. A cohort of 325 patients with whole genome RNA-seq expression data from the Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Furthermore, we compared the prognostic predictive abilities of 20 different risk signatures of gliomas in TCGA from published articles, including inflammatory response-related gene (IRRG) signature ( Yan et al, 2022 ), DNA damage and repair-related gene (DDRRG) signature ( Li et al, 2022c ), CXCR members signature ( He et al, 2022 ), pyroptosis-related gene signature ( Zhang M. et al, 2021b ; Chao et al, 2022 ; Yang et al, 2022 ; Zhang et al, 2022 ), ECM-related gene (ECMRG) signature ( Li et al, 2022b ), tripartite motif (TRIM) family gene signature ( Xiao et al, 2022 ), antigen presentation machinery (APM) signature ( Chen et al, 2022 ), natural killer cell-related gene (NKRG) signature ( Li C. et al, 2022a ), IL-4-related gene (IL4RG) signature ( Qi et al, 2022 ), hypoxia-related gene (HRG) signature ( Gao et al, 2021 ), S100 family-based signature ( Hu et al, 2021 ), TIME signature ( Zhang C. et al, 2021a ), focal adhesion-related gene (FARG) signature ( Li et al, 2021 ), m6A RNA methylation regulator signature ( Cong et al, 2021 ), HDAC1-related signature ( Fan et al, 2021 ), RNA-binding protein (RBP)-based signature ( Chen et al, 2021a ) and ferroptosis-related gene (FRG) signature ( Chen et al, 2021b ). The results of univariate and multivariate Cox analyses showed that our ARG signature had independent predictive ability ( p < 0.001, Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we compared the prognostic predictive abilities of 20 different risk signatures of gliomas in TCGA from published articles, including inflammatory response-related gene (IRRG) signature ( Yan et al, 2022 ), DNA damage and repair-related gene (DDRRG) signature ( Li et al, 2022c ), CXCR members signature ( He et al, 2022 ), pyroptosis-related gene signature ( Zhang M. et al, 2021b ; Chao et al, 2022 ; Yang et al, 2022 ; Zhang et al, 2022 ), ECM-related gene (ECMRG) signature ( Li et al, 2022b ), tripartite motif (TRIM) family gene signature ( Xiao et al, 2022 ), antigen presentation machinery (APM) signature ( Chen et al, 2022 ), natural killer cell-related gene (NKRG) signature ( Li C. et al, 2022a ), IL-4-related gene (IL4RG) signature ( Qi et al, 2022 ), hypoxia-related gene (HRG) signature ( Gao et al, 2021 ), S100 family-based signature ( Hu et al, 2021 ), TIME signature ( Zhang C. et al, 2021a ), focal adhesion-related gene (FARG) signature ( Li et al, 2021 ), m6A RNA methylation regulator signature ( Cong et al, 2021 ), HDAC1-related signature ( Fan et al, 2021 ), RNA-binding protein (RBP)-based signature ( Chen et al, 2021a ) and ferroptosis-related gene (FRG) signature ( Chen et al, 2021b ). The results of univariate and multivariate Cox analyses showed that our ARG signature had independent predictive ability ( p < 0.001, Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphisms in the interleukin-4 receptor genes are associated with better OS in Glioma patients [ 31 ]. The interleukin-4-related genes have a prognostic value for Glioma [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the high-risk group showed enrichment of more types of immune cells than the low-risk group, Treg cells and M0 macrophages have been reported to play an immunosuppressive role in gliomas, and Treg cells, neutrophils and M0 macrophages are associated with the malignant clinical features of gliomas, indicating the predominance of cancer-promoting immune cells in the high-risk group. [39][40][41][42] The monocytes that were enriched in the low-risk group were antigen-presenting cells that elicited significant antitumor effects. [43] Interestingly, the levels of infiltrating CD8 + and CD4 + T cells in high-risk patients with gliomas were higher than those in low-risk patients.…”
Section: Discussionmentioning
confidence: 99%